2007
DOI: 10.1161/atvbaha.107.150698
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Activation by Oxidized Low Density Lipoprotein Is Mediated by Cd36 and Scavenger Receptor-A

Abstract: Objective-The interaction of platelets with low density lipoprotein (LDL) contributes to the development of cardiovascular disease. Platelets are activated by native LDL (nLDL) through apoE Receptor 2Ј (apoER2Ј)-mediated signaling to p38 MAPK and by oxidized LDL (oxLDL) through lysophosphatidic acid (LPA) signaling to Rho A and Ca 2ϩ . Here we report a new mechanism for platelet activation by oxLDL. Methods and Results-Oxidation of nLDL increases p38MAPK activation through a mechanism that is (1) independent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 40 publications
5
80
0
1
Order By: Relevance
“…Interestingly, our experiments with TSP-1 demonstrate that JNK lies downstream of Src family kinases, since JNK phosphorylation was blocked by PP1, which is consistent with other studies demonstrating that oxLDL activates a CD36-Src family kinase-JNK pathway in platelets. 25,40 However, our data suggests a divergence in the mechanisms through which Src kinases regulate cAMP/PKA and JNK. It is possible that activation of Src family kinases downstream of CD36 ligation could therefore reduce platelet sensitivity to inhibition by the cAMP/PKA pathway but also increase platelet activation through phosphorylation of JNK.…”
Section: Thrombospondin-1 Inhibits Camp/pka Signaling 4303mentioning
confidence: 70%
See 1 more Smart Citation
“…Interestingly, our experiments with TSP-1 demonstrate that JNK lies downstream of Src family kinases, since JNK phosphorylation was blocked by PP1, which is consistent with other studies demonstrating that oxLDL activates a CD36-Src family kinase-JNK pathway in platelets. 25,40 However, our data suggests a divergence in the mechanisms through which Src kinases regulate cAMP/PKA and JNK. It is possible that activation of Src family kinases downstream of CD36 ligation could therefore reduce platelet sensitivity to inhibition by the cAMP/PKA pathway but also increase platelet activation through phosphorylation of JNK.…”
Section: Thrombospondin-1 Inhibits Camp/pka Signaling 4303mentioning
confidence: 70%
“…We show for the first time that TSP-1 stimulates CD36-mediated signaling events in platelets without inducing aggregation, which is consistent with recent studies demonstrating CD36-dependent stimulation of MAPKinases by oxLDL, without causing platelet aggregation. 25,40 Together, these data suggest CD36-mediated signaling in plays a secondary rather than primary role in platelet function. Based on our data, it is possible that previous studies highlighting the activatory and potentiating effects of CD36 ligands such as TSP-derived peptides, 7,8 oxLDL, 24 and VLDL 25,42 on platelet function could be due, at least in part, to their ability to modulate cAMP-PKA signaling events.…”
Section: Thrombospondin-1 Inhibits Camp/pka Signaling 4303mentioning
confidence: 87%
“…4,6,7,20 Through this mechanism pathologic ligands generated in the context of hyperlipidemia and/or inflammation and oxidant stress enhance platelet reactivity and contribute to a prothrombotic state. Using oxLDL as a model ligand, we found that the initial signaling events triggered by CD36 involve liganddependent recruitment and activation of specific src family kinases Fyn and Lyn.…”
Section: Discussionmentioning
confidence: 99%
“…3,5 OxLDL and oxPC CD36 also bind to platelets via CD36 leading to platelet activation. 4,6,7 This process may contribute mechanistically to the well known clinical association between hyperlipidemia, oxidant stress, enhanced platelet reactivity, and the prothrombotic state. 4 The mechanism by which CD36-oxLDL interactions promotes platelet reactivity is not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Human platelets were isolated 14 while maximally preventing their activation using free-flow blood collection and discarding the first 2 mL of blood and all collections that showed microaggregates as determined by particle sizing. The procedures were approved by the Medical Ethical Committee of our hospital; the laboratory is certified for ISO-9001:2008.…”
Section: Platelet Isolation and Incubationsmentioning
confidence: 99%